Christian College, Christian Calling Higher Education in the Service of the Church - Wilkens, Steve; Paul Shrier; Ralph P. Martin (Lanham AltaMira Press, 2005)
Christian colleges have been set up by Christian churches throughout American history. But all too often these schools and the groups that support them come into conflict, typically over what is being taught in religion and philosophy classes.
Keywords: Education (Christian theology) Christian universities and colleges